Engineering Tissue-Informed Biomaterials to Advance Pulmonary Regenerative Medicine - Campbell, Donald R.; Senger, Christiana N.; Ryan, Amy L.; Magin, Chelsea M. (Frontiers in Medicine, 2021)
Biomaterials intentionally designed to support the expansion, differentiation, and three-dimensional (3D) culture of induced-pluripotent stem cells (iPSCs) may pave the way to cell-based therapies for chronic respiratory diseases. These conditions are endured by millions of people worldwide and represent a significant cause of morbidity and mortality. Currently, there are no effective treatments for the majority of advanced lung diseases and lung transplantation remains the only hope for many chronically ill patients. Key opinion leaders speculate that the novel coronavirus, COVID-19, may lead to long-term lung damage, further exacerbating the need for regenerative therapies. New strategies for regenerative cell-based therapies harness the differentiation capability of human iPSCs for studying pulmonary disease pathogenesis and treatment. Excitingly, biomaterials are a cell culture platform that can be precisely designed to direct stem cell differentiation. Here, we present a closer look at the state-of-the-art of iPSC differentiation for pulmonary engineering, offer evidence supporting the power of biomaterials to improve stem cell differentiation, and discuss our perspective on the potential for tissue-informed biomaterials to transform pulmonary regenerative medicine.